2023
DOI: 10.5703/1288284317625
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Traffic Signal Performance Measures: Leveraging Connected Vehicle Data

Abstract: High-resolution connected vehicle (CV) trajectory and event data has recently become commercially available. With over 500 billion vehicle position records generated each month in the United States, these data sets provide unique opportunities to build on and expand previous advances on traffic signal performance measures and safety evaluation. This report is a synthesis of research focused on the development of CV-based performance measures. A discussion is provided on data requirements, such as acquisition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Over the last few years, crowdsourced connected vehicle (CV) trajectory data has emerged as a new dataset capable of producing and expanding existing traffic signal and arterial performance measures [7,[22][23][24][25][26][27][28][29][30][31][32][33]. With over 500 billion records generated each month in the United States, CV data enable the development of highly scalable techniques since no detection or communication equipment is required.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last few years, crowdsourced connected vehicle (CV) trajectory data has emerged as a new dataset capable of producing and expanding existing traffic signal and arterial performance measures [7,[22][23][24][25][26][27][28][29][30][31][32][33]. With over 500 billion records generated each month in the United States, CV data enable the development of highly scalable techniques since no detection or communication equipment is required.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various traffic signal performance measures have been developed in the last two decades that enable the assessment of progression and capacity utilization at intersections [6][7][8]. A popular metric used to evaluate intersection congestion is the occurrence of split failures, also known as cycle failures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging connected vehicle (CV) data can act as an alternative data source to potentially deliver a more scalable method to measure temporal and spatial usage of passenger vehicles in near real-time for a variety of applications, including trip origin-destinations, quantifying traffic congestion, travel mode choice, traffic safety, and infrastructure planning [16][17][18][19][20]. Early studies have shown that these CV datasets capture around 500 billion vehicle records in a month nationwide [21] for the United States, with a rough market penetration of 5-7% [22].…”
Section: Emerging Connected Vehicle Data Opportunitiesmentioning
confidence: 99%
“…This data has already shown wide-ranging applicability to prioritize traffic signal retiming, monitor mobility in varying weather conditions, and assess work zone mobility [20,23,24]. Including additional probe, CV data sources provide unique opportunities to evaluate transportation infrastructure and prioritize investments, including pavement markings, pavement quality, and the deterioration of roadway conditions during winter storms using friction data [21,25].…”
Section: Emerging Connected Vehicle Data Opportunitiesmentioning
confidence: 99%